Mengapa Orang Mengunggah Isu Pemilu Di Media Sosial?: Motivasi Trolling - Lestari, Laila Indra; Vardia, Melly Amalia (Flourishing Journal, 2022)
Abstract: We live in the age of technological abundance in the twenty-first century. The arrival of networked digital machines and information flow is slowly but steadily shaping practically every aspect of our daily lives. Social media platforms, for example, provide a new mode of communication that allows users to engage in discussions and exchange opinions on a variety of topics, fostering global dialogue. As is happening in today's politics, social media is a dangerous threat to democracy and pluralism. Social media, as it is in today's politics, is a dangerous threat to democracy and pluralism. We are witnessing the birth of a new political language game, with trolling as one of the primary moves, as a result of the rise of social media. Social media not only poses a unique threat to local politics but also global peace and stability. The purpose of this study is to explain why trolls spread rumors on social media. This study was conducted on netizens who actively engaged in trolling behavior. We used a qualitative paradigm with a phenomenological approach to investigate the role of motivation in trolling behavior to share substantiated and unsubstantiated content of the Indonesian election. Results show that trolling is motivated by two factors, according to the findings: intrinsic motivation (i.e. problem-solving, education, and seeking attention, as well as supporting social factors) (i.e. environment and timing). Abstrak: Di abad ke-21, kita hidup di era teknologi yang berkembang sangat cepat. Keberadaan media digital dan informasi perlahan namun pasti memengaruhi hampir setiap elemen dari kehidupan kita sehari-hari. Misalnya, platform media sosial memberikan bentuk pola komunikasi baru yang memungkinkan seseorang terlibat dalam diskusi dan bertukar pendapat tentang berbagai topik. Kemudahan dalam berkomunikasi ini menciptakan dialog pada skala global. Seperti dalam politik kontemporer yang terjadi saat ini, media sosial adalah ancaman berbahaya yang dapat disalahgunakan untuk demokrasi dan pluralisme. Dengan maraknya media sosial, muncul permainan bahasa politik baru, salah satunya disebut dengan trolling. Fokus penelitian ini adalah mengeksplor motivasi troll yang membagikan informasi dan rumor di media sosial. Penelitian ini dilakukan pada netizen yang berpartisipasi aktif dalam perilaku trolling. Untuk mengeksplorasi peran motivasi perilaku trolling untuk berbagi konten pemilu Indonesia, kami menggunakan paradigma kualitatif dengan pendekatan fenomenologis. Hasil temuan menunjukkan bahwa faktor yang memotivasi netizen melakukan trolling yakni motivasi intrinsik yang meliputi topik yang menarik, memenuhi kebutuhan emosional dan kebutuhan kognitif, motivasi ekstrinsik yang meliputi problem solving, education, dan mencari perhatian, serta faktor sosial pendukung yang meliputi lingkungan dan waktu.